2019
DOI: 10.3389/fmicb.2019.02271
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Successions of Common and Rare Bacteria in Soil Under Humic Acid Amendment – A Microcosm Study

Abstract: Humic acid (HA) is widely used for soil quality improvement, yet little is known how bacterial communities, especially common and rare bacteria, respond to HA amendment, which is crucial to understand biodiversity and function in agroecosystem. Therefore, a manipulated microcosm experiment with a gradient of HA amendment was conducted to unveil this. The results showed that common and rare taxa had similar patterns in species richness, while rare taxa exhibited a higher turnover, which caused their higher stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…Species with wider niche breadth are considered to be generalists which are less influenced by environmental factors because of higher environmental tolerances (49,50). In our study, habitat niche breadth of fungi continuously increased along with soil depth (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Species with wider niche breadth are considered to be generalists which are less influenced by environmental factors because of higher environmental tolerances (49,50). In our study, habitat niche breadth of fungi continuously increased along with soil depth (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Collectively, the results suggested the importance of the deterministic and stochastic processes that complementarily and simultaneously governed the bacterial community across the soil profiles. The abundant groups in the bacterial communities were further parsed to better understand the taxon-specific selection and dispersal mechanisms (27)(28)(29). In our opinion, the type of ecological processes structuring the assembly of the bacterial phyla was depth dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In a long-term fertilization experiment, a rare soil bacterial community, rather than a dominant soil bacterial community, controlled multiple ecosystem functions [ 3 ]. Li et al (2019) observed distinct changes in rare and abundant bacteria in response to humic acid amendment [ 4 ]. Similarly, a previous study reported that different patterns were observed between rare and abundant taxa in oil-contaminated soils [ 5 ].…”
Section: Introductionmentioning
confidence: 99%